2014
DOI: 10.1093/molehr/gau044
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual blood-derived stromal stem cells from women with and without endometriosis reveal different phenotypic and functional characteristics

Abstract: Retrograde flow of menstrual blood cells during menstruation is considered as the dominant theory for the development of endometriosis. Moreover, current evidence suggests that endometrial-derived stem cells are key players in the pathogenesis of endometriosis. In particular, endometrial stromal stem cells have been suggested to be involved in the pathogenesis of this disease. Here, we aimed to use menstrual blood, as a novel source of endometrial stem cells, to investigate whether stromal stem cells from endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 73 publications
9
70
0
5
Order By: Relevance
“…Maguer‐Satta et al showed that a gradient of peptides generated by CD10 enzyme cleavage is involved, with β1‐integrins, in maintaining mammary stem cells and regulating their conversion to luminal progenitors . CD10 expression by stem cells in the bone marrow, adipose tissue, umbilical cord, hair follicle, and endometrium has been reported . CD10 has also been described as a cancer stem cell marker and its expression associated with metastasis and poor survival .…”
Section: Discussionmentioning
confidence: 99%
“…Maguer‐Satta et al showed that a gradient of peptides generated by CD10 enzyme cleavage is involved, with β1‐integrins, in maintaining mammary stem cells and regulating their conversion to luminal progenitors . CD10 expression by stem cells in the bone marrow, adipose tissue, umbilical cord, hair follicle, and endometrium has been reported . CD10 has also been described as a cancer stem cell marker and its expression associated with metastasis and poor survival .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, its role in endometriosis is not completely understood. Some authors have described increased IFN-γ mRNA expression in endometriosis compared to eutopic endometrium (12). It is known that IFN-γ inhibits the proliferation of human endometrial epithelium (14), but the resistance of endometriotic cells to IFN-γ-induced cell growth inhibition and apoptosis has been found to be a possible mechanism in endometriosis pathogenesis, and, at the same time, it seems that IFN-γ peritoneal fluid (PF) levels could be suppressed in endometriosis patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of MCP-1 in peritoneal fluid and endometrial glands of endometriosis patients have been recently reported (12). Thus, a higher concentration of MCP-1 might be partly responsible for higher IFN-γ production by monocytes and macrophages.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, an adequate decidualization process is indispensable for successful embryo implantation and development [82]. During this process, the endometrial stromal cells undergo phenotypic changes reminiscent of mesenchymal-epithelial transition leading to epitheloid cells [83,84,85], accompanied by changes in expression and localization of numerous cell–cell contact proteins.…”
Section: Cell–cell Junctions During Implantation and Decidualizationmentioning
confidence: 99%